Young Linguists' Insights: Taking interdisciplinary approaches to the fore - Połczyńska, Monika; Pakuła, Łukasz Piotr; Jaworska, Dorota (Wydział Anglistyki UAM, 2013)
Young Linguists’ Insights, an edited collection, offers a fresh perspective on a number of current issues in interdisciplinary linguistics. Both renowned specialists and junior researchers present the output of their work in 30 chapters grouped into six thematic sections. The scope of the publication encompasses sociolinguistics, neuro- and psycholinguistics, language and technology as well as more traditional approaches to language.
The edited collection offers an excellent selection of articles from various fields of linguistic inquiry authored by distinguished scholars and beginning linguists who are just starting to uncover new dimensions in linguistic research. This juxtaposition fills the volume both with the first-class expertise and original, brave perspectives on the presented topics ranging from sociolinguistics to issues in language and technology. I appreciate the breadth of the investigated contexts, the unique interdisciplinary perspectives adopted by the researchers as well as engaging international examples. Joanna Pawelczyk Faculty of English Adam Mickiewicz University in Poznań
This volume anthologizes the research of a wide range of interdisciplinary themes introduced by experts in the field followed by qualitative and quantitative articles by young international linguists interfacing language with society and discourse, technology, meaning, mind and brain, the press and formal and applied linguistics. The contributions represent a plethora of specific topics such as language extinction and revival, persuasive language, style, metaphor, syntax, semantics, speech perception and recognition, idiomaticity, irony, bilingualism, and developmental and clinical issues, among others, in many diverse languages. Yishai Tobin Ben-Gurion Univeristy of the Negev
Keywords: interdisciplinarity; linguistics; discourse; corpus linguistics; psycholinguistics